(untitled) (Baghdad Science Journal, 2025)
The activity of Adhatoda vasica crude plants extracts against B.thuringiensis bacteria was determined by MIC test and sensitivity test which showed no response of this type of bacteria against extracts .The interference between the effect of hot and cold aqueous extracts and Bacillus thuringiensis bacteria for controlling the population of fig moth when males and females released before treatment under control condithion was gave a highly percentage of larval mortality which reached to 100% in (B.t. + hot aqueous extract ) and 97.3% in (B.t + coldaqueous extract ) after two weeks of treatment when concentration of 50% of aqueous extracts and 5×10?1of Bacillus thuringiensis bacteria but when the insect (males & females) released after the dates treated with B.t & hot aqueous extract , the mortality was 100% in all first instar larvae. The results also showed that when treatment of the dates before the insects released more influence than that treated the date after the insects released so the percentage of mortality of larvae reached to 100% in first method and to 86.0% in second methods .